Constructed movements : extraction and resistance in Mexican migrant communities - Shah, Ragini (Race, labor migration, and the law ;, 2025)
"At once theoretically sophisticated and poignantly written, Constructed Movements centers stories from communities in Mexico profoundly affected by emigration to the United States to show how migration extracts resources along racial lines. Ragini Shah chronicles how three interrelated dynamics-the maldistribution of public resources, the exploitation of migrant labor, and the US immigration enforcement regime-entrench the necessity of migration as a strategy for survival in Mexico. She also highlights the alternative visions elaborated by migrant community organizations that seek to end the conditions that force migration. Recognizing that reform without recompense will never right an unjust migratory system, Shah concludes with a forceful call for the US and Mexican governments to make abolitionist investments and reparative compensation to directly counteract this legacy of extraction"--